Antibiotic Susceptibility Rates In Nosocomial Pseudomonas aeruginosa Isolates (Annals of Medical Research, 2021)
Aim: This study aims to investigate antibiotic resistance rates of 110 Pseudomonas aeruginosa strains isolated from nosocomial infections.
Keywords: emPseudomonas aeruginosa; /em Antibiotic Resistance; Nosocomial Infection.